Evaluación del extracto de guayusa (ilex guayusa loes) en terneros de 1 día a 3 meses de edad como promotor de crecimiento en la provincia de Napo-Baeza - Erazo Paucar, Erik Marcelo (2015)
This refer relates to the use of Guayusa extract (Ilex Guayusa Loes) in calves from 1 day to 3 months old as growth promoter in the province of "Napo-Baeza, which was raised for the general objective assessment of Guayusa extract in calves from 1 day to 3 months old as growth promoter for height and weight got in calves, b giving them milk and Guayusa extract to prevent enteric diseases and promote the efficient development and determine whether it is feasible and profitable to use Guayusa extract as growth promoter in the early stages of life of the calf. For the study, is used 10 Holstein calves of 1 day old , the same as they were separated in two treatments, 5 steers calves for each treatment, T1 which is considered as the control group, with traditional way. It means that every day was given two liters of milk either in the morning and afternoon, T2 same process was used with the difference that the milk was applied once a day 10 ml of Guayusa extract. The results of the research conducted to Guayusa extract that was a positive benefit in terms of development to get height and weight in calves , These results are favoring the financial study and may be considered as growth promoter....